ANALISA VALUE CREATION PADA PERGURUAN TINGGI - Devina Kamandhanu (Business Accounting Review, 2013)
In this era of globalization, the competition in the Universities industry is becoming increasingly fierce. Universities should create value, by providing the benefits and costs in accordance with the expectations of students. The purpose of this study was to measure value creation based on perception of the students majoring in accounting in private universities in by gender, grade, and seniority of students. The data were collected by distributing questionnaires to 135 accounting students at four private universities that have the highest tuition fee for their accounting program. To avoid any misinterpretation of the data obtained in the research process, there were several steps that must be passed as to test the validity and reliability testing. The variables tested by using One Way ANOVA test The results obtained from these test are there is significant differences in value creation based on student’s gender, and there are no differences in value creation based on score and seniority of the students.